2012
DOI: 10.1074/jbc.m112.393678
|View full text |Cite
|
Sign up to set email alerts
|

The mRNA-stabilizing Factor HuR Protein Is Targeted by β-TrCP Protein for Degradation in Response to Glycolysis Inhibition

Abstract: Background: HuR regulates expression of many oncogenic proteins by modulating mRNA stability. Results: Glycolysis inhibition facilitates HuR degradation through a novel ␤-TrCP-mediated mechanism. Conclusion: This mechanism underlies the complexity in the regulation of HuR turnover under different stress stimuli. Significance: The ability of glycolysis inhibitors to target expression of oncogenic proteins by promoting HuR degradation might foster novel strategies for cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 36 publications
0
54
1
Order By: Relevance
“…Abdelmohsen et al 22 showed that HuR protein reduction following heat shock involved HuR ubiquitination of lysine residue 182, nucleocytoplasmic transport and check-point kinase 2-mediated phosphorylation. Chu et al 28 also showed that, following the treatment of glucose transport inhibitor (CG-5), HuR was ubiquitinated and degraded via a mechanism involving the beta-transducing repeat-containing protein (β-TrCP1) complex, PKCα-mediated phosphorylation and HuR nucleocytoplamsic translocation. In both of these studies, HuR ubiquitination was shown to lead to protein degradation; however, the exact mechanisms including the E3 ligase(s) involved in HuR ubiquitination were not revealed.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Abdelmohsen et al 22 showed that HuR protein reduction following heat shock involved HuR ubiquitination of lysine residue 182, nucleocytoplasmic transport and check-point kinase 2-mediated phosphorylation. Chu et al 28 also showed that, following the treatment of glucose transport inhibitor (CG-5), HuR was ubiquitinated and degraded via a mechanism involving the beta-transducing repeat-containing protein (β-TrCP1) complex, PKCα-mediated phosphorylation and HuR nucleocytoplamsic translocation. In both of these studies, HuR ubiquitination was shown to lead to protein degradation; however, the exact mechanisms including the E3 ligase(s) involved in HuR ubiquitination were not revealed.…”
Section: Discussionmentioning
confidence: 95%
“…The ECRG2 V30E mutant failed to induce cell death and neither activated caspases nor suppressed XIAP and HuR (Figures 4 and 5). The information gathered in our study (Table 1) indicates that ECRG2 mutations could be found in various human malignancies and their distributions appear to be largely localize within a small region (a.a. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. This information could suggest that this region (a.a.27-44) may be commonly targeted by mutations and is important for ECRG2's function and/or regulation.…”
Section: Discussionmentioning
confidence: 96%
“…Migration and invasion were also impaired in cancer cells expressing the nonphosphorylatable HuR mutant S318A and enhanced in cells expressing the phosphomimetic mutant S318D . In breast cancer cells undergoing apoptosis in response to doxorubicin, HuR was phosphorylated at S221 and S318; in prostate cancer cells, PKC‐mediated phosphorylation on HuR S318 triggered the cytoplasmic export of HuR, which permitted the recognition of HuR by the E3 ubiquitin ligase βTrCP1 and its subsequent ubiquitin‐dependent degradation …”
Section: Hur Phosphorylationmentioning
confidence: 99%
“…In addition, over-expression of deubiquinating enzymes of the UBP family also altered the half-life of a GM-CSF ARE containing mRNA reporter, suggesting that the degradation of RNA and AUF1 protein components of an mRNP may be temporally correlated [115]. Since then several RNA binding proteins such as HuR [116], TTP [117], and SLBP [47] have been shown to be polyubiquitinated.…”
Section: Ubiquitin-dependent Pathwaysmentioning
confidence: 99%